Cambridge handbook of open strategy - Seidl, David 1971-; Whittington, Richard 1958-; Krogh, Georg von 1963- (Cambridge University Press, 2019)
The first of its kind, this Handbook mobilizes research on an emerging phenomenon, Open Strategy. As new technologies and societal pressures have precipitated employees, business partners, shareholder groups and other stakeholders into deeper involvement in strategy, various Open Strategy initiatives now promise greater transparency and inclusion in the strategy process. Providing a wide-ranging introduction to the concept of Open Strategy and its various dimensions, the chapters of this Handbook detail key practices, discuss the roles of technology, and propose various theoretical perspectives for researching Open Strategy. Finally, this Handbook addresses the ongoing challenges and politics involved in Open Strategy. It will appeal to organization and strategy scholars, master's students in business and management, practitioners, such as consultants and strategy staff in established firms, and anyone concerned with new trends in strategy development and its implications for organizations and their members
Keywords: Strategic planning; Management; Strategische Planung; Aufsatzsammlung